Subnational REDD+ Implementation: A Synthesis of Opportunities and Challenges - Youjin Jung; Joonsoon Kim (Land)
REDD+ is a global mechanism that reduces greenhouse gas emissions by preventing deforestation and forest degradation, enhancing forest carbon stocks, and promoting sustainable forest management in developing countries. It plays a crucial role for developing countries in achieving climate targets under the Paris Agreement and can be implemented at the project, subnational, and national levels. Subnational REDD+ offers several advantages over project-level, such as reduced risk of overestimating emissions and enhanced management of leakage. However, the comprehensive opportunities and challenges of subnational REDD+ have not been extensively investigated in the literature. This paper aims to undertake a thorough review of subnational REDD+, highlighting its potential and the obstacles it faces. This systematic review synthesizes the existing literature on subnational REDD+ implementation, analyzing 54 peer-reviewed articles published between 2005 and 2024. The review identified three key factors for the effective implementation of subnational REDD+: financial, social, and institutional factors. Within these three factors, both opportunities and challenges were discussed, drawing on case studies and synthesizing practical implications. Our findings demonstrate that successful subnational REDD+ initiatives require integrated approaches that address the causal relationships between financing mechanisms, governance structures, and stakeholder engagement. The discussion further explores these interdependencies, revealing how constraints in one dimension create cascading effects across others. This study provides empirical insights and actionable recommendations for policymakers and project developers engaged in climate change mitigation efforts.